2021
DOI: 10.1016/j.cmi.2020.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antimicrobial stewardship based on rapid phenotypic antimicrobial susceptibility testing for bacteraemia in patients with haematological malignancies: a randomized controlled trial

Abstract: Objectives: Recently, rapid phenotypic antimicrobial susceptibility testing (AST) based on microscopic imaging analysis has been developed. The aim of this study was to determine whether implementation of antimicrobial stewardship programmes (ASP) based on rapid phenotypic AST can increase the proportion of patients with haematological malignancies who receive optimal targeted antibiotics during early periods of bacteraemia. Methods: This randomized controlled trial enrolled patients with haematological malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…Meanwhile, the use of broad spectrum antibiotics over the course of a week was similar for both groups. This is different from the results of previous studies [ 23 ], which may be due to the smaller sample size and the higher proportion of multidrug-resistant strains in both groups in this study. This suggests the need for further studies to evaluate the utility of dRAST for reducing use of broad spectrum antibiotics use during a pandemic.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the use of broad spectrum antibiotics over the course of a week was similar for both groups. This is different from the results of previous studies [ 23 ], which may be due to the smaller sample size and the higher proportion of multidrug-resistant strains in both groups in this study. This suggests the need for further studies to evaluate the utility of dRAST for reducing use of broad spectrum antibiotics use during a pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…), delivers antimicrobial susceptibility test results within 6 h after a Gram smear examination by analyzing changes in the morphology of a single bacterial cell under various antibiotic conditions [ 22 ]. dRAST can accelerate administration of optimal antibiotics and reduce use of broad spectrum antibiotics [ 23 24 ]. However, clinical application of dRAST has not yet been established widely, especially during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, patients with hematologic malignancies and bacteremia were randomized to receive either the rapid testing method or conventional testing, which consisted of MALDI-TOF and MicroScan (Beckman Coulter Inc., Atlanta, GA) and VITEK 2 systems (bioMérieux, Inc.) for AST. Time to optimal therapy was significantly faster in the rapid testing arm than in the control arm, although there were no differences in mortality or other clinical outcomes (76). Taken together, these studies demonstrate that a variety of rapid AST methods can shorten time to optimal therapy and improve antibiotic stewardship for patients with bloodstream infections.…”
Section: Clinical Impact Of Rapid Antimicrobial Susceptibility Testinmentioning
confidence: 73%
“…Notably, the impact on antibiotic utilization varied by resistance profile of the blood isolate; compared with the SOC arm, in the rapid testing arm, time to any Gram-negative antibiotic change occurred 24 h faster for all patients, and antibiotic escalation occurred 43 h faster for patients with drug-resistant isolates (19). Lastly, a recent small study from Korea evaluated the impact of a rapid phenotypic AST method based on a microscopic imaging and microfluidic chip technology called dRAST (QuantaMatrix) (76). In this study, patients with hematologic malignancies and bacteremia were randomized to receive either the rapid testing method or conventional testing, which consisted of MALDI-TOF and MicroScan (Beckman Coulter Inc., Atlanta, GA) and VITEK 2 systems (bioMérieux, Inc.) for AST.…”
Section: Clinical Impact Of Rapid Antimicrobial Susceptibility Testinmentioning
confidence: 99%
“…Once the patient is on treatment, RDTs can inform the decision on whether to target or broaden therapy. In a randomized, controlled trial of 116 Korean patients with hematologic malignancies and at least 1 positive blood culture, rapid phenotypic antimicrobial susceptibility testing was associated with a significant reduction in the proportion of patients receiving unnecessary broad-spectrum antimicrobials compared with conventional methods (12.5% vs 30.0%, respectively; P = .031) [ 20 ]. Similarly, a Japanese study found that use of a syndromic PCR panel in patients with bacteremia supported rapid susceptibility testing, and antimicrobial prescription changes were instituted in around one-quarter of cases [ 21 ].…”
Section: Delphi Consensus Statementsmentioning
confidence: 99%